Evaluation of blood parameters changes of mice exposed to long-term Wi-Fi waves as a major environmental pollutant - Hamed Akbari; Lobat Taghavi; Seyed Kamal Eshagh Hossaini; Mohammad Gholami-Fesharaki; Seyed Alireza Hajiseyed Mirzahosseini (Anthropogenic Pollution)
As the world entered the industrial era, the nature of environmental threats and dangers posed by technology also have gone through fundamental changes. One of these environmental pollutants is the propagation of waves with different wavelengths in the environment. In this study, we aimed to investigate the effect of 2.45 GHz microwaves on blood biomarkers of mice. In this study, 80 immature male BALB/c mice were used. According to the inclusion criteria, 72 mice were included in the study. Mice were divided into two groups (control group=24 mice, exposed group=48 mice). Exposed groups were divided into two subgroups of 24 (groups A and B). Subgroup A was exposed to a simple modem without antenna and subgroup B was exposed to a modem with two antennas. In the first phase of the study, mice were exposed daily for 60 minutes for 90 days and in the second phase for 8 hours daily for 90 days. Blood samples were taken on days 90 and 180. Data analysis was done by SPSS software version 25 (P value<0.05). This study shows that blood cells are affected by long-term exposure to Wi-Fi waves by decrease in number and volume. Furthermore, no significant difference was observed between the blood parameters of the two groups exposed to different modems which vary in the number of antennas. The results showed that the highest effect of Wi-Fi waves was on the following blood factors, respectively PLT, RBC, HCT, HGB, and WBC.